A seleção de macrófitas aquáticas com potencial para remoção de metais-traço em fitorremediação - Andre Baxter Barreto (2011)
A substantial and positive effect of the presence of macrophytes in the removal of pollutants has been shown in most researches comparing planted and unplanted subsurface flow constructed wetlands (CW) for the treatment of effluents. Aquatic macrophytes are a major component in constructed wetland systems since they are directly or indirectly related with pollutant removal mechanisms associated to these systems. Time and again the presence of macrophytes has been proved beneficial; nevertheless, it is not yet clear whether different forms and sizes of plant species exhibit relevant differences when it comes to efficiency in the removal of specific pollutants. Although many researches demonstrate that such differences do exist, it is not yet possible to generalize about the specific capabilities of each plant species. Thus, it can be stated that the selection of macrophyte species in constructed wetland and phytoremediation systems is an important project component and deserves greater attention. This research has investigated the bioaccumulation of heavy metals (Cr, Cu, Pb, Ni, V and Z) in macrophytes growing naturally in contaminated areas in order to evaluate the accumulation capabilities of these elements in different species and to discuss their potential use in constructed wetland and phytoremediation systems. Plants were collected in two urban areas and one naturally preserved area, identified and prepared for heavy metal analysis. Results reveal different accumulation capabilities and suggest that certain species bear specific mechanisms that remove and translocate heavy metals from roots to stems and leaves. Out of seventeen genera ten have proved to be candidates for future research on heavy metal accumulation and use in constructed wetland and phytoremediation systems. These species have good biomass production, their root systems are generally well developed and they also resist flood conditions and high pollutant concentrations. They have presented positive results in studies conducted by other researchers. Such species are: Cardamine sp., Commelina sp., Eclipta sp., Eichhornia sp., Heteranthera sp., Ludwigia sp., Plantago sp., Polygonum sp., Sagittaria sp. and Typha sp.